Ovarian morphometric characterization and in vitro maturation of oocytes obtained from buffalo (Bubalus bubalis) ovaries - partial results - Leal, L. S. [UNESP] (2007)
Buffalo ovaries were collected from a slaughterhouse (Frigol, Brazil) and transported to the laboratory in saline solution at 36 degrees C. The ovaries were dissected to realize the evaluations (weight, length, width and height of the ovary; corpus luteum and dominant follicle diameters). The Cumulus-oocyte complexes (COCs) were recovered by aspiration of 2-8 mm follicles. Selected COCs were matured in TCM 199 supplemented with 10% fetal bovine serum, sodium pyruvate, LH, FSH, estradiol and gentamicin. In vitro maturation was carried out at 38.5 degrees C for 22-24 h and 34-36 h. For the evaluation of the nuclear maturation the oocytes were placed in TCM 199 medium added with type v hialuronidase where the granulosa cells were extracted. The denuded oocytes were transferred to 10 mu l of Hoescht 33342 and the chromosomic configuration was evaluated. The oocytes were classified according to meiosis stage in: Germinal Vesicle, Germinal Vesicle Breakdown, Metaphase I, Metaphase II and Degenerated. The means of weight, length, width and height of the ovary were 3.83 g, 2.27 cm, 1.08 cm and 1.56 cm, respectively. The means of corpus luteum and dominant follicle diameters were 1.40 cm and 7.77 mm. The proportion of oocytes that reached metaphase II stage was: 36.68%.